Rekonstruksi Tsunami Mentawai dengan Menggunakan COMCOT v1.7 - Ratuluhain, Eva Susan; Noya, Yunita A.; Pradjoko, Eko; Rahman, Rahman; Hukubun, Ronald D. (Politeknik Negeri Sambas, 2022)
Many studies on the Mentawai tsunami have been carried out. Still, not many have reviewed the validation of run-up height compared to the results of field studies in the same year as the Mentawai tsunami on October 25, 2010. The survey of the Mentawai tsunami reconstruction using COMCOT v1.7 aims to validate The tsunami run-up height of the model output was compared with the results of the field study by the GITST Team in 2010. Validation of the model was carried out using the Aida parameter, by calculating the ratio of the comparison between the model output and the field study results. The study location of the model is divided into 3 layers, namely layer01 covering Sipora Island, North Pagai Island, and South Pagai Island, layer02 covering North Pagai Island and South Pagai Island, and layer03 with the focus of observation on Sibigau Island, with bathymetric resolution used for each layer. 464 m, 232 m, and 77 m so that the propagation at the observation site can be seen clearly. The height of the modeled tsunami ranged from 2.5 – 11.2 meters, with a maximum run-up height observed on Sibigau Island of 11.2 meters, and the time range for the tsunami arriving on land was 5 – 15 minutes. The comparison ratio between the model results and the field study is K = 0.9 and k (standard deviation) = 0.16. Based on the comparison ratio, the model output is close to the actual result.